The importance of public procurement for the strategic objectives of national socio-economic development - Kokocińska, Katarzyna (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
The involvement of the public authorities in socio-economic processes serves to achieve the objectives of the adopted policy of the State (or, respectively, the European Union). The state’s policy devised to foster socio-economic development is an instance of active state interventionism. In Polish legislation, this policy has been defined by the legislator as development policy. The aim of this paper is to demonstrate that public procurement is an instrument for achieving the strategic objectives of the development policy, thus drawing on the concept of ‘strategic use of public procurement’: a particular notion of the role of public procurement in the context of the strategic approach to development. One of the premises here is that a specific public goal – whose achievement is desirable from the standpoint of public procurement law – should serve to achieve the strategic objectives of development policy law. The article underscores the instrumental (albeit crucial) nature of public procurement with respect to state policy. For the purposes of the study, it was assumed that failure to appreciate the essence of using public procurement in the pursuit of strategic development objectives will adversely affect the consistency of public objectives and, consequently, result in incoherent actions. In this context, the author assesses the provisions of the Public Procurement Law, which provides the grounds for the adoption of the national purchasing policy that emphasizes the relevance of linking public procurement with the achievement of state objectives. The article shows that the introduction of the obligation to prepare a state purchasing policy and linking this document with the system of strategic development planning confirms the strategic use of procurement, which should serve the implementation of important public interests.